South Pacific hydrologic and cyclone variability during the last 3000 years. (18th April 2016) - Toomey, Michael R.; Donnelly, Jeffrey P.; Tierney, Jessica E.
Abstract: Major excursions in the position of the South Pacific Convergence Zone (SPCZ) and/or changes in its intensity are thought to drive tropical cyclone (TC) and precipitation variability across much of the central South Pacific. A lack of conventional sites typically used for multimillennial proxy reconstructions has limited efforts to extend observational rainfall/TC data sets and our ability to fully assess the risks posed to central Pacific islands by future changes in fresh water availability or the frequency of storm landfalls. Here we use the sedimentary record of Apu Bay, offshore the island of Tahaa, French Polynesia, to explore the relationship between SPCZ position/intensity and tropical cyclone overwash, resolved at decadal time scales, since 3200 years B.P. Changes in orbital precession and Pacific sea surface temperatures best explain evidence for a coordinated pattern of rainfall variability at Tahaa and across the Pacific over the late Holocene. Our companion record of tropical cyclone activity from Tahaa suggests major storm activity was higher between 2600‐1500 years B.P., when decadal scale SPCZ variability may also have been stronger. A transition to lower storm frequency and a shift or expansion of the SPCZ toward French Polynesia around 1000 years B.P. may have prompted Polynesian migration into the central Pacific. Key Points: SPCZ migrated and/or intensified since 3200 years B.P. in response to orbital forcing Enhanced South Pacific (SP) cyclogenesis occurred between ~2600 and 1500 years B.P. Changes in SP rainfall ~1000 years B.P. may have prompted Polynesian expansion